ENGLISH TRANSLATION BASED COMMUNICATIVE E-MODULE DESIGN TRANSLATION APPROACH IN UNU-SMART DARING APPLICATION IN TRANSLATION COURSE - Ahmad Efendi; Diyah Dwi Agustina; Rahmat Basuki (Journal of English Educational Study (JEES), 2022)
Research on e-Modules was present learning packaged in one form of teaching materials in a systematic, easy to understand, interesting way so that it was easy to learn independently. This was in accordance with the times in the digital world, on the other hand, there was still an outbreak of the COVID-19 pandemic. The purpose of this research was designed an e-Module as a teaching material for fifth semester students of English Education in the smart UNU application. E-Model was an experience for prospective teacher students and has the ability to translate after graduating from college. As a support for the learning model to easily produce products, namely; Analysis, Design, Development, Implementation, Evaluation (ADDIE Model). The research has 3 (three) steps; Introduction, Development and Assessment. In stage (1) the Preliminary Study includes; study of translation theory in Education, communicative translation approach (CTA theory), UNU Online Smart software, (2) designing e-Modules, developing module assessment instruments, evaluation instruments, and (3) Product Testing Phase and a module-based communicative translation approach for English Language Education courses. The average value obtained was 43.31 with a good category based on the results of the validation analysis.